The Effect of Vitamin E on the Expression of Mitochondrial Apoptotic Pathway genes in the Cerebellar Tissue of the Parkinson’s Rat Model: Vitamin E on Mitochondrial Pathway Genes in Parkinson Rat Model - Jamali, Behdokht; Entezari, Maliheh; Babaei, Nahid; Hashemi, Mehrdad (Archives of Advances in Biosciences, 2021)
Introduction: Parkinson’s disease is one of the debilitating diseases which is more common amongst the elderly; oxidative stress has been found to be one of its major causes. In this study, therefore, the effect of vitamin E on the expression of Bcl-2 family genes was studied. Materials and methods: A total of 24 adult rats were purchased from the Pasteur Institute of Iran. The rats were later divided into 4 groups: control group, control group receiving VitE, PD group, PD group receiving VitE. After RNA extraction, cDNA synthesis, and primer design of Bax and Bcl-2 genes, their expressions were studied in different rat groups by RT-PCR technique. Results: The mitochondrial apoptotic gene expressions were affected by vitamin E administration. Vitamin E decreased the expression of Bax gene and overexpressed Bcl-2 gene. Conclusion: Vitamin E plays an important role in reducing the effects of oxidative stress and, consequently, apoptosis in the cerebellar tissue cells of rats with Parkinson’s disease.